Virtual centre for the rehabilitation of road accident victims (VICERAVI) - Mendes, Liliana (2019)
The main objective of this work is to describe the Virtual Center for the Rehabilitation of Road Accident Victims - VICERAVI and the serious games it includes for the purpose of neuropsychological rehabilitation. The validation of the VICERAVI as a rehabilitation system involves 30 participants of both sexes, with brain injury due to road accidents. The applicability and the benefits of virtual worlds for a holistic neuropsychological rehabilitation will be tested using virtual reality (OpenSimulator) to simulate tasks of everyday life, enabling participants to perform cognitive and social skills training through their avatars. The progresses of this group will be compared with a group of conventional neuropsychological rehabilitation. The main innovation of the work is the possibility of administering neuropsychological rehabilitation at distance, via ecological virtual environments. Moreover, the paper discusses also relevant criteria and issues in respect to the use of serious games, simulation and virtual environments in rehabilitation.